Discourse and Judicial Thinking — A Corpus-based Study of Court Judgments in Hong Kong, Taiwan and Mainland China - Cheng, Le (International Journal of Speech, Language and the Law, 2011)
Awarding Institution: City University of Hong Kong Date of Award: February 2010 Th is corpus-based study focuses on Chinese court judgments as a specifi c form of judicial discourse. Specifi cally, it examines the discursive representation of judicial thinking.